Expanding Our Knowledge of Menstrual Irregularities Reported by Females With Tuberous Sclerosis Complex - Mowrey, Kate; Northrup, Hope; Hashmi, Syed Shahrukh; Rodriguez-Buritica, David (Frontiers in Reproductive Health, 2022)
Purpose The purpose of our study is to expand the knowledge regarding intrinsic reproductive dysfunction in females with TSC and to explore the impact of mTOR inhibitors (mTORi) on menstrual irregularity in the Tuberous Sclerosis Complex (TSC) community. Methods An electronic survey composed of author-designed questions set out to evaluate reproductive history, presence of menstrual irregularities, mTORi use, as well as maternal reproductive history among females with TSC. Results Of the 68 responses from females with TSC regarding age of menarche, the average age was 12.3 years. 56.5% (n = 48) of respondents reported irregular menstrual cycles and noted a total of 102 menstrual irregularities. There was a cohort of 35 women with a reported history of mTORi use. Of these women, 68.6% (n = 24) reported irregular menstrual cycles after taking mTORi. In comparison, among the females with no history of mTORi use (n = 50) only 48% reported irregular menstrual cycles (n = 24). Conclusions Our data expands the knowledge regarding intrinsic menstrual dysregulation present in women with TSC, demonstrates a rate of menstrual irregularities among females taking mTORi, and identifies a tendency toward early menarche that may be a previously unrecognized feature of TSC.